Weighing temporal fluctuations of drought features in Rwanda through the implementation of the standardized precipitation evapotranspiration index and standardized precipitation index - Kazora Jonah; Zhu Weijun; Kyaw Oo Than; Temesgen Gebremariam Asfaw; Emmanuel Adu Gyamfi Kedjanyi; Abraham Okrah; Akimana Diane; Mathieu Mbati Mugunga (Environmental Research Communications)
Climate change poses significant challenges globally, affecting weather patterns and leading to more frequent and severe extreme events such as droughts. In Rwanda, a country highly reliant on rainfed agriculture, understanding the changing nature of droughts is crucial for effective climate adaptation and resilience-building efforts. This study investigates temporal variations in drought characteristics across Rwanda using the Standardized Precipitation Index (SPI) and the Standardized Precipitation-Evapotranspiration Index (SPEI). Through a comprehensive analysis spanning multiple time scales (3-month and 12-month periods) and spatial extents, the research assesses drought occurrence, frequency, intensity, and severity from 1983 to 2020. Utilizing the homogeneity test, Mann-Kendall trend test, and Sen’s slope method, the study identifies significant trends in precipitation, SPEI, SPI, potential evapotranspiration (PET), and trends in PET changes over time. Results reveal substantial spatial and temporal variability in drought patterns, with distinct interdecadal shifts observed. While certain regions experienced increased drought frequency and severity, others exhibited wetter conditions. Notably, the Eastern and Southern provinces faced intensified drought impacts, with prolonged dry spells lasting over 3 to 6 months. The research emphasizes the necessity of comprehending the temporal and spatial fluctuations in drought attributes to enhance agricultural practices and adaptation measures. Through the utilization of complementary drought indices and robust statistical approaches, this study offers valuable insights into Rwanda’s susceptibility to climate variability and its impacts on socio-economic advancement. The findings offer essential guidance for policymakers, stakeholders, and communities in developing targeted interventions to mitigate the adverse impacts of droughts and enhance resilience to climate change.